Determinants of e-Government Adoption in Libya: Examining the Mediating Effect of Trust - Amer Salem Ali Salem (Journal of Libyan Academy Bani Walid, 2025)
Governments are continuously striving to improve the services they offer to their citizens. The advent of e-Government (electronic government) has provided numerous advantages; however, citizens still have yet to engage with services that are offered. Most of the existing literature in this area appears to focus on developed countries, with few studies articulating the situation of e-government in developing countries. This research aims to outline the factors influencing the use of e-Government services in Libya. Using the existing literature, the research is developed around the Unified Theory of Acceptance and Use of Technology (UTAUT) and adds the factors of security and trust. The research adopts three main constructs; individual factors which consist of performance expectancy, effort expectancy, social influence and IT knowledge; technological factors which consist of facilitating conditions, security, and privacy; and trust which comprises trust in the government and trust in the Internet, with trust also analyzed as a mediating factor. This is a quantitative research study that uses a questionnaire as the main method of data collection. The questionnaire was administered to 320 respondents using stratified vector sampling from the population of the students and staff of the University of Tripoli (academic and administrative staff). The results suggested that both personal and technical factors are significant predictors of the intention to use e-Government services. The main predictors include performance expectancy, social influence, IT knowledge, trust in the Internet, facilitating conditions, privacy and security. Trust was shown to partially mediate between technical factors and behavioural intention. Increasing citizen participation in e-Government services could have a huge impact on improving public spending efficiency and public satisfaction.